Factors, drivers and barriers to improving hospital cost management: A Systematic review - Elahe Eyshi; Omid KHosravizadeh; Aisa Maleki; Bahman Ahadinezhad (Tehran University of Medical Sciences, 2022)
Aim & Background: Cost management is the most important factor affecting the economic performance of the hospital. Good management of costs in the short term stabilizes and balances the operating balance of the hospital and secures the hospital in terms of liquidity. Also, good management of costs in the long term makes the hospital financially stable. According to the mentioned cases and increasing hospital costs, the present study was conducted with the aim of identifying and investigating the factors, drivers and obstacles to improve cost management. Methods & Materials: This systematic review was conducted in 2020. Data was collected through  searching keywords in Google scholar, PubMed, Scopus, Web of Science, Science direct, Magiran, SID and Irandoc databases from 2007 to 2020. The classification of the results of the studies was done by the researchers. Results: All the components identified and extracted from the articles were divided into four dimensions (increasing factors, prerequisites, obstacles and solutions) to improve hospital cost management. Conclusion: Reviewing the results of each study showed the importance of each component in managing, improving and controlling hospital costs. In this regard, policy makers at decision-making level and managers at executive level should pay attention to the components and dimensions affecting the control and improvement of hospital costs according to the structure, process and expected consequences, and then decide on their implementation.